Presenting the direct intercultural effectiveness simulation: an implicit trait policy on intercultural competence - Schelfhout, Stijn; Derous, Eva (Frontiers in Psychology, 2023)
In a series of three studies (N1 = 224, N2 = 291, N3 = 478), the present research introduces a “Direct Intercultural Effectiveness Simulation” or DIES, an instrument that simulates intercultural effectiveness by directly tapping into an ITP on intercultural competence. An implicit trait policy (ITP) represents the interaction between a personal disposition and general domain knowledge on how to effectively handle a specific (intercultural) situation. Such an ITP is a proven construct to create instruments that can predict future effective behavior. Moreover, such a simulation can provide valuable proxies for actual (future) behavior, as measures of (future) real life intercultural interactions are not always available. First and foremost, the present research demonstrates that the DIES instrument generates reliable and construct-valid measures of intercultural effectiveness. Second, the DIES instrument also shows expected converging and diverging patterns when correlated with a nomological network on intercultural effectiveness. And third, the DIES measure is further validated by integration into an ITP framework of intercultural effectiveness based on theoretical and empirical accounts from literature. In practice, the DIES instrument can be used as an awareness or training proxy for actual behavior to tackle important problems like ethnic prejudice and discrimination.